The Gram-Schmidt method in the identification of a generalized control system - Wysocki, Hubert (Zielona Góra: Uniwersytet Zielonogórski)
This article discusses the identification of a generalized linear control system described in the Bittner operational calculus by an abstract linear differential equation with constant coefficients.
Keywords: operational calculus; derivative; integral; limit condition; control system; identification; orthonormalization method